Integrating Local Wisdom in Strengthening the Pancasila Student Profile - Maswati; Rosmiati Ramli; Sumiati Sumiati; Imam Pribadi; Faiq Athillah; Hadi Pajarianto (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The Pancasila Student Profile represents a concrete manifestation of the national education goals and serves as a fundamental reference in formulating educational policies, including religious literacy. This study aims to identify the noble values of local wisdom in South Sulawesi that contribute to the strengthening of the Pancasila Student Profile (P5), and explore the patterns of integrating local wisdom values into the implementation of P5. This research employs a qualitative descriptive approach. Data sources were selected using purposive sampling techniques. Data collection methods included observation, in-depth interviews, and documentation, with the researcher acting as the primary research instrument. The research findings confirm that local wisdom values have been incorporated into the learning process to strengthen the P5 program in schools. Each dimension of P5 includes elements of local wisdom: D1 incorporates the values of mallise ale and mabbokong; D2 integrates sipakatau, sipakainge, and sipakalebbi; D3 reflects asunpololo; D4 includes agettengeng; D5 emphasizes amaccang; and D6 upholds the value of reso. These values are embedded through intracurricular, cocurricular, and extracurricular activities. The intracurricular approach can also be implemented through project-based or problem-based learning models, encouraging students to think critically about local issues as a means of reinforcing national integration.